Morning heart rate variability as an indication of fatigue status in badminton players during a training camp - Iizuka, T.; Ohiwa, N.; Atomi, T.; Shimizu, M.; Atomi, Y. (Sports, 2020)
This study aimed to clarify whether changes in the fatigue status of elite athletes during a precompetition period could be evaluated using morning heart rate variability (HRV) indices. Eight Japanese National Badminton Team players (age, 23.0 ± 2.8 years) participated in this study. HRV and subjective fatigue were measured during the first (days 1-4: Phase 1) and the second half (days 5-8: Phase 2) of an 8-day national team training camp. The global and parasympathetic HRV indices were as follows: standard deviation of all R-R intervals (SDNN) (Phase 1, 87.5 ms; Phase 2, 104.3 ms; p < 0.05), root mean square of the successive R-R interval differences (RMSSD) (Phase 1, 66.6 ms; Phase 2, 103.6 ms; p < 0.05), and high-frequency component power (HF) (Phase 1, 1412.0 ms2; Phase 2, 3318.5 ms2; p < 0.05). All the aforementioned indices increased significantly from Phase 1 to Phase 2. Significant correlations were observed between the change in subjective fatigue and changes in SDNN, RMSSD, and HF (? = -0.80, p = 0.017; ? = -0.77, p = 0.027; and ? = -0.80, p = 0.017, respectively). Measuring morning HRV indices may be effective for objectively evaluating changes in the fatigue status of elite athletes during a precompetition period.